Road Traffic Noise and Self-Reported Sleep Disturbance: Results from a Cross-Sectional Study in Western India. (February 2013) - Banerjee, Dibyendu
Background: Previous studies have provided evidence about chronic night noise exposure and sleep disturbance, which is indicator of more serious health conditions. Such studies have never been reported for the Indian population. This study aimed to further explore the association between nocturnal transportation noise exposure and self-reported sleep disturbances in an adult Indian population. Methods: The cross-sectional study used results from a pilot study, from a large scale social survey in the urban municipality of Asansol, an industrial city, situated in western India. The survey included responses from 221 adults (19–59 year old) residing within 100 meters buffer of the major and arterial roadways, with criteria of minimum 10 years stay in the study area. Association of self-reported sleep disturbance was studied by multiple logistic regression analysis with adjusting for age, gender and period of residence. Results: Sleep disturbance was more marked at levels of 61–65 dB(A) night noise exposure, OR (95% CI) 2.36 (1.13–4.94. For a 5dB(A) increase in night noise exposure, the OR (95% CI) was 1.30 (1.04–1.64). For every 10 years addition to age of the respondents, odds of sleep disturbance was estimated to increase by 1.17 over non-exposure individuals. Women reported higher sleep disturbance, OR (95% CI) 1.23 (0.65–1.92) in comparison to men A period of residence of 10 years in study area showed an OR (95% CI) of 1.33 (0.86–2.06) for sleep disturbance among exposed respondents. Further it was estimated with 95% confidence that the attributable fraction for sleep disturbance among those noise exposed within the population was 16% to 80%. Conclusions: The study results support an association between higher nocturnal road traffic noise and self-reported sleep disturbance in comparison to areas with quieter nights. Further sleep disturbance among women was significantly associated with higher night noise exposure.